Factors Influencing Career Choice As An Entrepreneur In West Nusa Tenggara: A Quantitative Analysis Using Logistic Regression - Putri, Irma Apriliana; Emi Salmah; Muhammad Dzul Fadlli (International Journal of Economics, Business and Innovation Research, 2025)
This study uses logistic regression analysis to investigate the factors influencing career choice as an entrepreneur in West Nusa Tenggara. Data analysis from the National Labor Force Survey (SAKERNAS) explores key determinants such as gender, age, family status, work hours, training, and dependents. The findings reveal that gender has a negative and significant effect, indicating that males are less likely to become entrepreneurs than females, with a coefficient of -0.3535706. Age, family status, work hours, and the number of dependents all positively and significantly affect choosing a career as an entrepreneur. Specifically, individuals are more likely to become entrepreneurs with each additional year of age (coefficient = 0.0411477). Individuals with family are likely to engage in entrepreneurship, with a coefficient of 1.08056, and those with longer work hours are more likely to become entrepreneurs, with a coefficient of 0.0161729. The training was found to have a negative and significant effect, with a coefficient of -1.015992, indicating that individuals who have training are less likely to engage in entrepreneurial activities. The number of dependents also exhibited a positive impact, with a coefficient of 0.0386476, suggesting individuals with more dependents are more likely to pursue entrepreneurship.